The existential quest for freedom: Resistance and self-determination in Naguib Mahfouz’s Miramar - Zulhelmi, Anshar; Aminah, Siti; Tosimpak, Hasanuddin; Rifqi, Khairul; Muhyiddin, Luthfi (UIN Ar-Raniry Banda Aceh, 2025)
This study analyzes Naguib Mahfouz’s novel Miramar through the lens of existential feminism, focusing on the character of Zahra representing a young woman who struggles to free herself from the social, psychological, and cultural constraints that limit her freedom. This research employs a qualitative descriptive-analytical approach by examining Zahra’s actions, dialogues, internal monologues, and character development throughout the story. Simone de Beauvoir’s existential feminist theory is applied to explore themes of freedom, self-determination, and resistance against patriarchal hegemony. The findings reveal that Zahra’s rejection of an arranged marriage, her courage to leave her hometown, and her commitment to working at the Miramar pension symbolizes her existential struggle. Zahra also faces intimidation, discrimination, and harassment from male characters, yet she continues to maintain her dignity and control over her life. This underscores her struggle to gain bodily autonomy, identity, and a future of her own. By depicting Zahra’s determination to achieve economic independence and personal development, Mahfouz offers a social critique of gender inequality and the restricted roles of women in post-revolutionary Egyptian society. This study concludes that Miramar is not merely a portrait of Zahra’s personal conflict but also a powerful commentary on class, identity, and women’s struggle to create the meaning of their own lives. The study highlights the relevance of existential feminism in understanding the dynamics of women’s freedom and resistance in modern literature.